Analisis Keterlaksanaan Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka di Kelas X.12 Sekolah Menengah Tingkat SMA - Sriayu Lestari (PT PUSTAKA CENDEKIA GROUP, 2024)
Education is a conscious effort to acquire knowledge that cannot be separated from the curriculum as the main guide in the learning process. The Independent Curriculum, which began to be implemented in the 2022-2023 academic year, emphasizes freedom of learning and creativity in the learning process, one of which is through a differentiated learning approach. This approach aims to adjust learning to students' readiness, interests, and learning preferences in order to create an inclusive and adaptive learning environment. However, observation results show that the implementation of differentiated learning in schools still faces various obstacles, such as time constraints, administrative burdens, lack of supporting facilities, and challenges in accommodating the diversity of student characteristics. Therefore, support is needed from various parties, including schools and the government, in providing resources, professional training for teachers, and utilizing diagnostic tools to understand students' learning profiles. With the right strategy and collaboration between stakeholders, the implementation of differentiated learning can be optimized to achieve the goals of the Independent Curriculum in improving the quality of education that is more adaptive and inclusive.